Matsal dalam Perspektif Hadits Tarbawi: Studi atas Hadits tentang Perumpamaan Teman yang Baik dan Teman yang Buruk - Muhammad Fatih (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
Matsal is one of the most commonly used uslubs (language styles), both in profane and sacred texts, such as the scriptures. There are many verses in the Qur'an and the hadiths of the Prophet. using mass to convey religious messages. This is because the material is believed to help the reader to better understand, reflect on, and apply the message in the text. The language style matures, draws the reader closer to the meaning of the text, presents a concrete and tangible picture of abstract concepts and meanings, and trains the reader in his or her ability to determine aspects of appropriateness between what is said and interpreted. No less than a thousand hadith using mass. He makes good notes with expressions, gestures, pictures, and more. Even the Prophet. use a medium style of language whether at home or on the go, sleeping or waking and the situation between them. The Prophet's Prophet was not always dependent on himself, but also on Allah Almighty. and the angels. The themes developed are also varied, including the fields of faith, worship, morals, asceticism, fadhaail al-A'mal, tarhib, targhib, and more. The purpose is clear, to make it easier for people to understand the message. One of the hadith of the Prophet (saws). using the mass language style is a hadith about the imagery of good and bad friends. Good friends are likened and portrayed as perfumers, while bad friends are likened to blacksmiths. The perfume seller is identical to the scent, a clean and dignified place, a happy mood and a happy soul, like a heavenly atmosphere. While the blacksmith is identical to the hot air, the spark, and the unpleasant scent that is choking the chest, the fire is like hell. Being friends with the saints leads to heaven, and being friends with the wicked can lead to hell. At this point it is important that one is careful and selective in choosing friends and the social environment, because misunderstanding and choosing friends will result in great loss and destruction, both in the world and in the hereafter. The use of the mass language style in this hadith gives you a clear picture of who your best friends should follow, and who your best friends should avoid. The perspective of the celestial hadith in this study reveals the educational values ??contained in the Prophet's body.